ANALISIS IMPLEMENTASI, METODE, DAN EVALUASI PENDIDIKAN KARAKTER DI SEKOLAH DASAR DI SDN 21 TEMBAN KABUPATEN ENREKANG - Nirmayani Tiala; Suardi (STKIP Subang, 2026)
This study aims to analyze the implementation, methods, and evaluation of character education at SDN 21 Temban, Enrekang Regency. The study employed a qualitative approach through interviews, classroom observations, document analysis, and student focus group discussions. The results show that character education is explicitly stated in the school’s vision and mission. The school emphasizes the development of students who are disciplined, responsible, and respectful of others, indicating a strong institutional commitment to integrating character education as a core educational objective